Estudo da propriedade antiofídica de Jatropha Elliptica (pohl.) mull arg. - Rodrigues, Sára Costa Ferreira (Universidade Federal do Tocantins, 2021)
about 90% of them resulting in severe local and systemic changes which can leave serious sequelae or even lead to death. The commercial antivenom is ineffective against the local effects and the distance and difficulty to access the service locations are aggravating. Medicinal plants as Jatropha elliptica to treat snakebites is a valuable resource face to the biodiversity of Brazil. Proteomic studies of snake venoms demonstrate particularities regarding the composition and the relationship with the symptoms caused. Such particularities influence the treatment due to differences in the neutralizing capacity of the serum. The study of the composition of Bothrops moojeni puppies from the cerrado (TO) took into account the variations for the sex of these animals and evidenced significant differences between both, demonstrating a wide and diversified category of proteins. The venom of FIL ♀ (female puppies) presented MCD (Minimum Coagulant Dose) in 0.2 µg / mL of equine plasma and that of FIL ♂ (male puppies) 0.4 µg / mL, the female venom being the most coagulant. The venom of FIL ♀ stood out in the serine protease activity (0.34 ± 0.05 nmol), being superior to the activity of the venom of FIL ♂ (0.26 ± 0.03; p <0.001) and was also more lethal. However, these poisons did not differ in phospholipase and hemorrhage activities. The ability of the adult B. moojeni venom pool (50 µg / mL) to block the activity of the mice phrenic nerve diaphragm preparation was measured using a traditional myographic technique. The JeP (powder), obtained by hand from J. elliptica, was screened at concentrations of 100 and 1000 µg / mL and were tested by three protocols: a) pre-venom: JeP for 15 min, followed by the addition of poison; b) post-venom: poison for 15 min before adding JeP; and c) pre-incubation: a mixture of poison + JeP for 30 min before adding to the bath. For pre-venom and post-venom treatments with JeP 100 µg / mL, 100.9 ± 7.6% and 97 ± 6.1%, respectively. The pre-incubation model showed a similar effect (78.2 ± 9.2%) to those produced by commercial bothropic antivenom (80.2 ± 14.1%). In the same sequence of models, for JeP 1000 µg / mL, the T50s were 88.1 ± 7.7%; 61.5 ± 9.1%, and 86.5 ± 8.9%. The increase in JeP to 1000 µg / mL (10X) was negligible to improve the T50 of the poison. The results showed that Bothrops moojeni venom induces neuromuscular block and small amounts of the J. elliptica starch was efficient in reversing this effect.